The impact of service and goods offshoring on employment: Firm-level evidence - Carmine Ornaghi; Ilke Van Beveren; Stijn Vanormelingen (National Bank of Belgium, 2017)
Advances in communication technology have led to a remarkable increase in the tradability of services, resulting in a substantial increase in offshoring of services over the last two decades. Research investigating how this surge in service offshoring affects employment, has been largely hampered by the paucity of suitable microdata. This paper tries to fill this gap by using a newly constructed database of Belgian firms that combines individual transaction-level data on international trade in goods and services with annual financial accounts. This unusually rich dataset allows us to produce fresh evidence on the impact of goods and service offshoring on total employment and employment by educational levels for both manufacturing industries and the service sectors. Our results show that: (i) goods offshoring has a positive impact on employment growth among workers with both low and high levels of education in the manufacturing industry but this effect disappears when controlling for scale effects; and (ii) service offshoring has a negative impact on employment growth among highly educated workers in the service sectors. This novel evidence suggests that globalization may threaten job security of higher educated workers too.
Keywords: 330; Offshoring; trade in services; labour markets